2023
DOI: 10.1002/ael2.20116
|View full text |Cite
|
Sign up to set email alerts
|

The fate of nitrogen of ammonium phosphate fertilizers: A blind spot

Andrew J. Margenot,
Jeonggu Lee

Abstract: Ammonium phosphate fertilizers are a common phosphorus (P) source for crops, namely monoammonium phosphate, diammonium phosphate, and ammonium polyphosphate. Despite containing appreciable nitrogen (N), ammonium phosphate fertilizers are generally considered P fertilizers. However, the approximately 8.5 million Mg N co‐applied with P annually as ammonium phosphate fertilizers represents 8% of global N fertilizer input flux to agroecosystems. Despite this, a systematic review of the literature revealed only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In contrast with commonly used ammonium phosphates, the low water solubility of struvite could reduce P and N loss risk when used as a fertilizer (Margenot et al, 2019). However, no studies have tested hypothesized reductions of P and N losses under struvite relative to highly water-soluble ammonium phosphate fertilizers such as MAP at the field scale, perhaps in part because these fertilizers are categorized by the US Department of Agriculture as P and not N fertilizers (Decock, 2014;Margenot & Lee, 2023). Though N from fall-applied ammonium phosphates is assumed to be readily available in the spring, commonly perceived as a benefit of using these fertilizers as a P source (Maqsood et al, 2022;Pagani et al, 2013), limited field-scale evaluations have found that only 30% of the N applied in the fall as MAP or DAP was recovered in the spring as extractable soil inorganic N at 30-cm depth (Fernández et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with commonly used ammonium phosphates, the low water solubility of struvite could reduce P and N loss risk when used as a fertilizer (Margenot et al, 2019). However, no studies have tested hypothesized reductions of P and N losses under struvite relative to highly water-soluble ammonium phosphate fertilizers such as MAP at the field scale, perhaps in part because these fertilizers are categorized by the US Department of Agriculture as P and not N fertilizers (Decock, 2014;Margenot & Lee, 2023). Though N from fall-applied ammonium phosphates is assumed to be readily available in the spring, commonly perceived as a benefit of using these fertilizers as a P source (Maqsood et al, 2022;Pagani et al, 2013), limited field-scale evaluations have found that only 30% of the N applied in the fall as MAP or DAP was recovered in the spring as extractable soil inorganic N at 30-cm depth (Fernández et al, 2010).…”
mentioning
confidence: 99%
“…This suggests that two-thirds of N may have been lost from the rooting zone, likely via leaching and gaseous emissions (Fernández et al, 2010), though these loss pathways were not measured. Struvite is expected to have lower N leaching compared to MAP, reducing N losses that may occur during the offseason following fall application (Margenot & Lee, 2023). Field-scale evaluations of reduced P and N losses hypothesized for struvite relative to MAP or DAP are needed to quantify the extent to which P and N are leached.…”
mentioning
confidence: 99%